Pengembangan Sistem Inventory Praktikum Pemesinan Berbasis Web di Laboratorium Pemesinan Jurusan Teknik Mesin Fakultas Teknik Universitas Negeri Malang - Febri Eko Wijanarko (Universitas Negeri Malang, 2020)
Abstract: This research aims to create a web-based machining practicum inventory system program that can assist laboratory assistants and students in the process of borrowing practicum equipment, as well as facilitate laboratory assistants in monitoring and registering all equipment contained in the machining laboratory. In this study, the validation of the program has been developed by involving two experts, namely material experts and media experts. Validation have been use to determine the feasibility of the program that has been developed before it will be tested on students majoring in mechanical engineering. The results of trials product by respondents, there are two aspects which are assessed namely, material aspects and media aspects. The score obtained from the material aspect was 96.25% and 96.125% was obtained from the media aspect, so the total score obtained from trials to students majoring in mechanical engineering was 96.18%. Key words: inventory system, machining practicum, web